Mobile Banking Applications as a Tool for Developing Banking Services Marketing in Algeria: A Case Study of DigitBDL and WimpayBDL from BDL Bank - Karima ZIDANE (Journal of Excellence for Economics and Management Research, 2025)
In an era of digital transformation, mobile banking applications play a crucial role in enhancing banking services marketing and financial inclusion. This study examines the impact of mobile banking applications on marketing strategies within the Algerian banking sector, with a focus on two applications developed by the Local Development Bank (BDL): DigitBDL and WimpayBDL.Through a case study approach, the research highlights the functionalities, customer engagement strategies, and marketing advantages of these applications. The findings reveal that mobile banking apps improve accessibility, customer interaction, and service efficiency while overcoming traditional banking limitations.The study concludes that leveraging mobile banking applications as a marketing tool can enhance customer satisfaction, brand visibility, and financial inclusion in Algeria